Crowdsourcing and COVID‐19: How Public Administrations Mobilize Crowds to Find Solutions to Problems Posed by the Pandemic. (27th March 2022) - Colovic, Ana; Caloffi, Annalisa; Rossi, Federica
Abstract: We discuss how public administrations have used crowdsourcing to find solutions to specific problems posed by the COVID‐19 pandemic, and to what extent crowdsourcing has been instrumental in promoting open innovation and service co‐creation. We propose a conceptual typology of crowdsourcing challenges based on the degree of their openness and collaboration with the crowd that they establish. Using empirical evidence collected in 2020 and 2021, we examine the extent to which these types have been used in practice. We discuss each type of crowdsourcing challenge identified and draw implications for public policy.